PENGARUH KEPERCAYAAN MEREK DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS MEREK PT ALFA SCORP II MARELAN MEDAN - Lindawaty Lindawaty; Syawaluddin Syawaluddin (JURNAL BISNIS KOLEGA, 2022)
Loyal consumers are assets that are meaningful to the company, because in addition to consuming continuously they will also help to market the product to others, and as we know that marketing word of mouth (the word of mouth) is: the most marketing method effective and efficient. High consumer loyalty will certainly require a long time and a good strategy. The factors that will shape loyalty are brand trust and customer satisfaction. This study is to determine the effect of Brand Trust and Consumer Satisfaction on Brand Loyalty at PT. Alfa Scorpii Marelan both partially and simultaneously.This type of research is a quantitative descriptive method. The object of research in this study is the customer of PT. Alfa Scorpii Marelan totaling 150 people. The sampling technique uses the Slovin formula which produces a sample of 109 people, the data analysis technique used is multiple regression analysis, t-test, F-test, and coefficient of determination test.The results showed that partially and simultaneously brand trust and customer satisfaction affected their loyalty. Companies are advised to increase brand loyalty by increasing brand trust by approaching consumers and creating motorcycles with more interesting features and variations. In terms of customer satisfaction, companies are advised to open a suggestion box about customer satisfaction with Yamaha motorcycles. Companies are also advised to increase consumer confidence and safety in riding Yamaha motorbikes, overcome complaints related to Yamaha motorcycles such as durability and product reliability, improve service and establish good relationships with consumers in order to increase customer satisfaction so that Brand Loyalty increases.Â Keywords: Brand Trust, Consumer Satisfaction and Brand Loyalty